Perceptions of Environmentally Sustainable Fashion by Finnish 25–45-year-old Consumers - Oittinen, Tutta Anette (2024)
The fashion industry plays a significant role on a global scale, contributing not only to greenhouse gas emissions but also to various other forms of pollution and environmental impacts. Production practices have accelerated in recent decades despite increasing attention towards more sustainable processes. The industry also disposes large quantities of garments annually, further exacerbating its environmental footprint. The lack of cohesive and unequivocal definition for environmentally sustainable fashion complicates efforts to understand the concept and hinders transparency within the industry, but also leaves a possibility for the actors within it to cover environmental sustainability only partly. This Master's Thesis explores the perceptions of environmentally sustainable fashion among Finnish consumers, comparing them to definitions of environmental sustainability outlined in research.